2018
DOI: 10.1111/jam.13767
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic inactivation of Listeria innocua biofilms with food-grade photosensitizers: a curcumin-rich extract of Curcuma longa vs commercial curcumin

Abstract: Curcumin represents a promising alternative to the control of bacteria and bacterial biofilms in food products particularly in the case of meat products in which turmeric is used as spice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…2014; Bonifácio et al . 2018). The effect is usually attributed to the barrier imposed by the extracellular matrix, which limits PS and O 2 access to target cell structures, and to the ROS‐scavenging effect of extracellular polymeric substances (Kishen 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2014; Bonifácio et al . 2018). The effect is usually attributed to the barrier imposed by the extracellular matrix, which limits PS and O 2 access to target cell structures, and to the ROS‐scavenging effect of extracellular polymeric substances (Kishen 2017).…”
Section: Resultsmentioning
confidence: 99%
“…2014; Bonifácio et al . 2018). Recently, it has been discovered that the addition of nontoxic concentrations of inorganic salts like KI, KBr, KSCN or NaNO 2 , significantly potentiates the photosensitization process to the level of the complete eradication of the otherwise less susceptible microbial targets (Hamblin and Abrahamse 2018; Santos et al .…”
Section: Introductionmentioning
confidence: 99%
“…Luksiene and Paskeviciute [ 48 ] found that Listeria monocytogenes biofilms on a food-related surface, polyolefine, were completely eliminated by 150 μmol/L Na-chlorophyllin followed by 5 min irradiation (λ = 405 nm). More recently, Bonifácio et al [ 49 ] observed L. monocytogenes biofilms reductions from 1.3 × 10 7 CFU/mL to 1.7 × 10 2 after PDI with curcumin at 3.7 mg/L and 30 min of light exposure (λ = 400–500 nm). Notably, comparing the present results with the above-mentioned studies, higher PS concentrations were needed to cause inactivation of Listeria spp.…”
Section: Discussionmentioning
confidence: 99%
“…Bonifácio et al. () compared the efficacy of a curcumin‐rich extract of Curcuma longa to that of commercial curcumin in aiding photodynamic inactivation of Listeria innocua biofilms. Using a 400 to 500 nm light source and an irradiance of 150 mW/cm 2 , the team observed that pre‐incubation with the natural extract for 30 min helped to bring about a 2‐ or 3‐log reduction, depending on the extract's concentration (0.6 or 1.1 μg/mL, respectively).…”
Section: In Vitro Pdi Of Foodborne Microorganismsmentioning
confidence: 99%